Pembuatan Vidio Promosi Café Luminary Menggunakan Teknik Live Shoot Dan Motion Graphic - Intan Gelar Nusa; Agusdi Syafrizal; Subhan Hartanto (JURNAL VOKASI TEKNIK, 2026)
Café Luminary, located in Samarinda, carries a classic concept with indoor and outdoor areas. The promotion of the café has so far only relied on Instagram and word-of-mouth communication, making it less optimal in reaching a wider audience. This research aims to create a promotional video by utilizing live shoot and motion graphic techniques. The live shoot technique is used to capture the authentic atmosphere of the café and customer activities, while motion graphics add dynamic visual elements to make the information more interesting. This research was conducted through three main stages: pre-production (idea design, screenwriting, and storyboarding), production (live shooting and creating graphic elements), and post-production (video editing using CapCut). The 1-minute 30-second promotional video was publicized through social media and other digital platforms. The results show that this combination of techniques is effective in increasing the visual appeal and competitiveness of the promotion. The resulting promotional video is expected to strengthen Café Luminary's branding, increase public awareness, and attract more visitors.